Unknown yogini - Temples of India Project Team (Jio Institute, 2024)
This is one of the many images of yoginis found at the site hinting towards a lost yogini temple compound. Contextualizing this image with several other relevant images suggests a maturity of Shakti and tantric traditions at the site. The placid expressions of this two-armed yogini seated in the lalitasana pose suggest her benevolent nature.